The Effect of Natural Fermentation of Cow Milk and Goat Milk to Flavor, Total Acid and Protein Concentration - M. A., Afifi; Okarini, I. A.; Mariani, N. P. (Jurnal Peternakan Tropika; Vol 6 No 3 (2018), 2018)
The study aim to determine the effect of the natural fermentation of cow milk and goat milk to flavor (taste and aroma), total acid and protein concentration. The samples were fresh Frisian Holstein Crossbreed (FHC) cow milk, and Etawa Crossbreed (PE) goat milk. Those were obtained from CV. Margo Utomo, located at Pulau Batam Street, No.10, Denpasar and a distributor of fresh goat milk was UD. Bali Sariwangi, located at Sepang Village, Busungbiu, Buleleng, Bali. The experimental design used was Randomized Block Design (RBD) consisted of 2 factors and 3 replicated. The first factors were milk type, namely S1 (100% cow milk), S2 (50% cow milk+50% goat milk) and S3 (100% goat milk). The second factors were fermentation time, i.e. W0 (control), W10 (10 hours of fermentation) and W20 (20 hours of fermentation). The variables observed were: flavor (taste and aroma), total acid and protein concentration. The result showed that milk type was not significantly differen (P>0,05) on taste and aroma, while the total acid and protein concentration were significant differen (P<0,05). The fermentation time was significantly different (P<0,05) to taste, aroma, the total acid and protein concentration. The interaction between milk type and fermentation time was significantly differen (P<0,05) to taste whereas in aroma, total acid and protein concentration were not significantly diferen (P>0,05). Based on the result of the study, it can be concluded  that the type of milk does not affected the taste and aroma of sour milk, but could increase total acid and reduce protein concentration during 20 hours fermentation. The fermentation time could increased total acid and reduce protein concentration, and reduce the score of panelis preference for taste and aroma of sour milk. There were interaction on taste. To make nature mixed milk and goat milk fermentation for 10 hours, due to it has no effect on taste and aroma, and total acid andprotein concentration is still in accordance with the standard, so it still suitable for consumsion and acceptable to consumers. Keywords: natural fermentation, cow milk, goat milk, total acid, protein, flavor.